Every random choice rule is backwards-induction rationalizable - LI, Jiangtao (Institutional Knowledge at Singapore Management University, 2017)
Motivated by the literature on random choice and in particular the random utility models, we extend the analysis in Bossert and Sprumont (2013) to include the possibility that players exhibit stochastic preferences over alternatives. We prove that every random choice rule is backwards-induction rationalizable.